An archaeological radiocarbon database for southern Africa. (August 2019) - Loftus, Emma; Mitchell, Peter J.; Ramsey, Christopher Bronk
Abstract: Abstract : The Southern African Radiocarbon Database (SARD) is a new online, open-access database of published radiocarbon dates from southern African archaeological contexts. Compatible with the calibration, Bayesian modelling and mapping functionality of the OxCal software, the SARD will greatly assist in the documentation and analysis of chronological trends across the subcontinent. This article introduces the database and presents two case studies that demonstrate its utility and its integration with OxCal, comparing the temporal distribution of radiocarbon dates in two archaeologically well-investigated regions, and assessing the timing of Middle to Later Stone Age technological developments across the African subcontinent.